CLASSROOM MANAGEMENT SKILLS IN TEACHING ENGLISH IN SECONDARY AND HIGHER EDUCATION AS A SECOND LANGUAGE - N.I.Turayeva (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article explores essential classroom management skills for teaching English as a Second Language (ESL) in secondary and higher education. It emphasizes the importance of creating a positive and supportive learning environment, establishing teacher authority, managing time efficiently, and engaging students through active participation. The article highlights practical strategies such as using error-friendly approaches, implementing differentiated instruction, and incorporating technology to enhance learning and classroom dynamics. It also addresses how to handle behavioral issues and adapt teaching methods to meet the diverse needs of students. Overall, the article provides valuable insights and strategies to help ESL educators effectively manage their classrooms and create an engaging and productive language-learning experience.